1999
DOI: 10.1177/101053959901100104
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus and Associated Cardiovascular Risk Factors in North-East Malaysia

Abstract: Two thousand five hundred and eight subjects from the state of Kelantan in North-East Peninsular Malaysia were included in this study to determine the prevalence of diabetes mellitus and impaired glucose tolerance and their association with cardiovascular risk factors. The overall prevalence of diabetes mellitus was 10.5% and impaired glucose tolerance was 16.5%. There was no difference in the prevalence of diabetes mellitus between males and females but the prevalence of impaired glucose tolerance was higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 6 publications
2
23
0
Order By: Relevance
“…12,13 An increasing number of hospital-acquired C. difficile infections have been reported among our patients with T2DM, especially in those admitted into acute medical wards, but its rate and associated risk factors are not known. A literature review found few relevant studies, thus prompting our review.…”
mentioning
confidence: 99%
“…12,13 An increasing number of hospital-acquired C. difficile infections have been reported among our patients with T2DM, especially in those admitted into acute medical wards, but its rate and associated risk factors are not known. A literature review found few relevant studies, thus prompting our review.…”
mentioning
confidence: 99%
“…A higher proportion of patients who came to the ED were found to have a higher prevalence of hypertension, diabetes mellitus, and mental disorders, which reflects the prevalence of chronic diseases in this country [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…A community that has high prevalence of obesity also has high prevalence of diabetes [36]. In Kelantan, Malaysia, the prevalence of diabetes in 1999 was 10.5%, and impaired glucose tolerance was 16.5% [39]. Kelantan is ranked highest in prevalence of diabetes in Malaysia in which the overall national prevalence is 8.3% [40], thus it was not a surprise to see a rapid rise of cancer prevalence in the state [36].…”
Section: Cancer: the Global Epidemicmentioning
confidence: 99%